The Plot to Kill God: Findings from the Soviet Experiment in Secularization - Anderson, John (A journal of church and state, 2009)
The aim of this book is both commendable and ambitious, in that it attempts “to take what historians and area specialists currently know about the Soviet Union and apply it to theoretical debates in the social scientific study of religion” (p. 15). In particular, it suggests that what is described as the “Secularization Experiment” tested the extent to which religious vitality or decline are a product of “ignorance, ritual activity, social institutions, social rewards, salvation incentives, and church-state relationships” (p. 24).